Quality of life of parents of school age children with a birth weight less than 1500 grams - Leticia Alcántara-Canabal; Lucía Martínez-Pérez; Sara Gutiérrez-Alonso; Cristina Fernández-Baizán; Marta Méndez (Elsevier, 2019)
Introduction: The birth of a preterm child has a high family emotional cost. The aim of this study is to assess the quality of life of parents of children aged 5-7 years born prematurely (<1500 g). Participants and methods: This is a cross-sectional study of a sample of parents of preterm infants admitted to a third level hospital in Spain between 2009 and 2011. Their infants weighed less than 1500 g at birth, and were 5-7 years old at the moment of the study. Parents completed the Parental Stress Scale, Family Apgar, Zarit modified scale, and Graffar-Méndez Castellano method (1994). A total of 94 cases were analysed (40 girls and 54 boys). Results: All data passed normality assumptions. Results showed no gender, weight or gestational age differences in our sample on the Zarit modified scale, Parental Stress Scale, or by the Graffar method. Differences between boys and girls were found in the Family Apgar test. Also, the Graffar method and degree of familiar malfunction showed significant results. The parents of preterm children with developmental problems at the time of the study showed significant differences with respect to parents of children without these problems in the Family Apgar test and the Zarit modified scale. Conclusions: The possible impact of the birth of a preterm child with less than 1500 g of weight is not appreciated between 5 and 7 years of age, except for the differences found in the perception of family functionality and caregiver overload among parents of children with and without developmental alterations. Resumen: Introducción: El nacimiento de un hijo prematuro conlleva un alto coste emocional familiar. El objetivo es valorar la calidad de vida de los progenitores de una cohorte de niños prematuros nacidos con peso menor de 1.500 g, cuando estos contaban entre los 5 y los 7 años de edad. Pacientes y métodos: Estudio transversal de encuestas personales a progenitores de niños de entre 5 y 7 años de edad que estuvieron ingresados en un hospital terciario de España entre 2009 y 2011, siendo neonatos, por un peso al nacimiento menor de 1.500 g. Se aplicó la escala del estrés parental, test de Apgar familiar, escala de sobrecarga del cuidador de Zarit y cuestionario Graffar. Se analizan 94 casos (40 niñas y 54 niños). Resultados: Todas las escalas muestran puntuaciones de normalidad. Con la escala de Zarit, del estrés parental y el cuestionario Graffar-Méndez Castellano, los resultados no reflejan diferencias por sexo, peso ni edad gestacional. Encontramos diferencias estadísticamente significativas con el test de Apgar familiar por sexo y entre la puntuación de Graffar y el grado de disfunción familiar. En el momento del estudio, los padres de niños con problemas en el desarrollo presentaban diferencias estadísticamente significativas con los padres de niños sin alteraciones, reflejadas en el test de Apgar familiar y en la escala de Zarit. Conclusión: La posible repercusión del nacimiento de un hijo con un peso menor de 1.500 g no se aprecia con los test estudiados cuando el niño tiene entre los 5 y 7 años de edad, salvo por las diferencias que se observan en la percepción de la funcionalidad familiar y en la sobrecarga de cuidadores entre los padres de niños con alteraciones en el desarrollo y sin ellas.